DAYA SIMPAN BENIH BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU PADA BERBAGAI PAKET TEKNOLOGI MUTU BENIH - Karim Andi Ete, Adrianton, Syarifudin (AGROTEKBIS, 2015)
Business development potential is quite large shallot cultivation. This certainly needs to be balanced with the procurement of quality seeds. One effort in this process is the improvement of quality seeds to be used, especially the seed storability. This study aims to determine the shelf life of various seed quality  packages. This research was conducted in May and July 2014 at the Laboratory of Seed Science and Technology, Faculty of Agriculture, University of Tadulako. This study used a completely randomized design (CRD) with 10 package of seed quality technology and 3 replications.. The treatments tested were P1 = Hanging, a height of 100 m above sea level, small tubers, 250 kg KCl / ha, P2 = Hanging, a height of 100 m a.s.l, large tubers, 100 kg KCl / ha, P3 = Hanging, a height of 100 m a.s.l, tubers large, 250 kg KCl / ha, P4 = Hanging, a height of 300 m a.s.l, large tubers, 100 kg KCl / ha, P5 = Hanging, a height of 300 m a.s.l, large tubers, 150 kg KCl / ha, P6 = Hanging, height 500 m a.s.l, large tubers, 150 kg KCl / ha, P7 = Protolan, a height of 300 m a.s.l, small tubers, 150 kg KCl / ha, P8 = Protolan, a height of 300 m a.s.l, large tubers, 150 kg KCl / ha, P9 = Protolan, a height of 500 m a.s.l, small tubers, 200 kg KCl / ha, and P10 = Protolan, a height of 500 m above sea level, large tubers, 200 kg KCl / ha. Data were analyzed by ANOVA test followed HSD 5%. The results showed storability of onion seeds in a package of technologies by hanging, altitude 500 MPL, and large tubers and giving 150 KCl / ha, produces the highest moisture content of 79.75% at 8 MSP, and the highest growth rate 46.50 % / etmal.